Copy of jquery.easing.min

Copy of jquery.easing.min - /* * jQuery Easing v1.1 -

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: /* * jQuery Easing v1.1 - http://gsgd.co.uk/sandbox/jquery.easing.php * * Uses the built in easing capabilities added in jQuery 1.1 * to offer multiple easing options * * Copyright (c) 2007 George Smith * Licensed under the MIT License: * http://www.opensource.org/licenses/mit-license.php */ jQuery.easing={easein:function(x,t,b,c,d){return c*(t/=d)*t+b},easeinout:function(x,t,b,c,d){if(t<d/2)return 2*c*t*t/(d*d)+b;var a=t-d/2;return-2*c*a*a/(d*d)+2*c*a/d+c/2+b},easeout:function(x,t,b,c,d){return- c*t*t/(d*d)+2*c*t/d+b},expoin:function(x,t,b,c,d){var a=1;if(c<0){a*=-1;c*=- 1}return a*(Math.exp(Math.log(c)/d*t))+b},expoout:function(x,t,b,c,d){var a=1;if(c<0){a*=-1;c*=-1}return a*(-Math.exp(-Math.log(c)/d*(t-d)) +c+1)+b},expoinout:function(x,t,b,c,d){var a=1;if(c<0){a*=-1;c*=- 1}if(t<d/2)return a*(Math.exp(Math.log(c/2)/(d/2)*t))+b;return a*(-Math.exp(- 2*Math.log(c/2)/d*(t-d))+c+1)+b},bouncein:function(x,t,b,c,d){return c- jQuery.easing['bounceout'](x,d-t,0,c,d)+b},bounceout:function(x,t,b,c,d)jQuery....
View Full Document

This note was uploaded on 02/21/2012 for the course COMP comp 111 taught by Professor Xyz during the Winter '12 term at University of Phoenix.

Ask a homework question - tutors are online